HUBUNGAN ANTARA INDIKATOR MIKRO DAN MAKRO TERHADAP NILAI BUKU DAN HARGA PASAR SAHAM PERUSAHAAN - Renata H Jacob; Sofyan S Harahap (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2007)
This study discusses the differences between Book Value and Market Value of Indonesian Company listed in .1SE focuses on banking industry which sample total 11 banks. The data was collected from financial reports of those banks published in the Indonesian Capital Market Directory of 19982002. The objective of the study was to test the differences between book value and market value of banks' shares using Tobin Q-Ratio model. Then, micro aspects are represented by EPS, LDR and ETA and macro aspects are represented by inflation and interest rate were examined how much those variables influence book value and market value. The study found that there was a difference between book value and market value. Average Q-Ratio Indonesian banking industry during 1999-2002 respectively was 1.72, 1.27, 0.92, 1.10 and 1.25. The highest and the lowest 0 ratio during 4 years in average was achieved by FT Bank CIC International Tbk 4,14 and PT Bank Pan Indonesia Tbk 0.27 respectively. Then, the correlation between independent and dependent variables using SPSS version 10 has been tested and found that micro aspect only influences 45.8% to book value and 61.7% to market value. EPS has more significant role in influencing book value and market value. Macro aspect has a minimum role in influencing. The limitation of this study is due to limitation of sample, period and ratio tested. Future research could be done in having more sample periods and ratios.Keywords: Measurement, Valuation, Book Value, Market Value, Financial Ratio, micro and macro aspects.